Penerapan Gaya Desain Post-Modern pada Perancangan Interior Pusat Edukasi Mitigasi Bencana di Yogyakarta - Sofia Veronica; Stephanus P Honggowidjaja (Intra, 2014)
Indonesia is a country with a high enough intensity of disasters. This is due to the geographical location of Indonesia which lies in the path of the Pacific Ring of Fire which is the most active zone of the row of the active volcanic mountain in the world. Against the backdrop of this, ‘The Interior Design of Disaster Mitigation Education Center in Yogyakarta’ facilitates the community to explore the causal and the mystery behind these natural phenomena interactively with dynamic atmosphere and distinct space design. Presenting an interactive and literated design, interior design involves direct experience of visitors to try simulations of natural disasters. In order to give personal experience of disaster response with the experts, this facility will be completed with various supporting facilities like science lounge, mini theater, lobby, gift shop, and a consistory area. The application of post-modern design style and dynamic design is expected to introduce a modern educational with cultural aspects implemented in the design.